The relationship between content textbook analysis and students’ achievements in the topic of ratio and proportion - Shamsuri, Syahindah (2025)
This study investigates the relationship between the distribution of mathematics textbook content and student achievement in the topic of ratio and proportion under the Malaysian KSSR curriculum. Prior research highlights that textbooks often prioritize procedural approaches, which can limit students' conceptual understanding and reasoning skills. To explore this, a sequential mixed-methods design was employed in three phases. Phase One involved a content analysis of Form One mathematics textbooks using the Level of Cognitive Demand (LCD) framework, categorizing problems into three dimensions: missing value, comparison, and qualitative. Phase Two assessed 302 students using 12 proportional reasoning test items. Phase Three consisted of interviews with three students to gain deeper insight into their thinking processes. Participants were sampled randomly from a population of 1,424 Form One students in the Kapar area of Klang, Selangor. The textbook analysis revealed a heavy emphasis on missing value problems (57.9%), which were mostly at Level 2, focusing on procedural understanding. In contrast, comparison and qualitative problems were less frequent but tended to appear at higher cognitive levels (Levels 3 and 4), particularly qualitative problems, which were all at Level 4. Student performance aligned closely with textbook emphasis. The highest scores were recorded for missing value problems (M = 7.82), followed by comparison (M = 2.37), and the lowest for qualitative problems (M = 0.61). This suggests that students are more proficient in procedural tasks but struggle with conceptual and reasoning-based problems. A significant positive correlation was found between the frequency of a problem type in textbooks and student achievement in that type. These findings underscore the importance of balancing procedural and conceptual content in textbooks and teaching practices to enhance students’ proportional reasoning and problem-solving abilities.